2016
DOI: 10.1098/rsbl.2016.0315
|View full text |Cite|
|
Sign up to set email alerts
|

Agonistic urban birds: elevated territorial aggression of urban song sparrows is individually consistent within a breeding period

Abstract: Urban birds often more vigorously defend their territories during simulated intrusions than do their rural counterparts, but the factors responsible remain unclear. To address this issue, we investigated whether the disparity in territorial aggression of urban and rural male song sparrows, Melospiza melodia, is individually consistent within a breeding period. Additionally, to better understand the physiological and ecological factors underlying this behavioural difference, we examined whether territoriality w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
40
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 14 publications
6
40
2
Order By: Relevance
“…The ornithological literature already offers many examples of adjustments in urban birds compared to rural conspecifics that are concordant with this expectation (see recent review in Marzluff, 2017). Urban birds are usually more aggressive (e.g., Minias, 2015;Davies and Sewall, 2016), bolder (e.g., Ducatez et al, 2017), can be approached more closely by humans (e.g., Lin et al, 2012;Møller et al, 2015), are less neophobic (e.g., Tryjanowski et al, 2016), have higher levels of disturbance tolerance (Lowry et al, 2013) and reduced levels of physiological stress response (e.g., Partecke et al, 2006;Minias, 2015). Other empirical comparisons between urban and rural birds have also suggested shifts in breeding strategies: urban birds usually have earlier laying dates, smaller clutch sizes, lower reproductive success (e.g., Peach et al, 2008;review in Chamberlain et al, 2009), and higher adult survival rates (e.g., Rebolo-Ifran et al, 2015).…”
Section: Introductionmentioning
confidence: 54%
“…The ornithological literature already offers many examples of adjustments in urban birds compared to rural conspecifics that are concordant with this expectation (see recent review in Marzluff, 2017). Urban birds are usually more aggressive (e.g., Minias, 2015;Davies and Sewall, 2016), bolder (e.g., Ducatez et al, 2017), can be approached more closely by humans (e.g., Lin et al, 2012;Møller et al, 2015), are less neophobic (e.g., Tryjanowski et al, 2016), have higher levels of disturbance tolerance (Lowry et al, 2013) and reduced levels of physiological stress response (e.g., Partecke et al, 2006;Minias, 2015). Other empirical comparisons between urban and rural birds have also suggested shifts in breeding strategies: urban birds usually have earlier laying dates, smaller clutch sizes, lower reproductive success (e.g., Peach et al, 2008;review in Chamberlain et al, 2009), and higher adult survival rates (e.g., Rebolo-Ifran et al, 2015).…”
Section: Introductionmentioning
confidence: 54%
“…Song sparrows are an excellent illustration of this, as multiple research groups have shown that urban male song sparrows are more aggressive toward conspecifics than their rural counterparts (Evans et al, 2010;Foltz et al, 2015b;Davies and Sewall, 2016). Further, male song sparrows living in urban habitats are more bold in response to heterospecific alarm calls and human approach than are rural males, though only response to alarm calls is correlated with conspecific aggression (Evans et al, 2010;Scales et al, 2011;Myers and Hyman, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have failed to find reliable differences in levels of the avian stress hormone, corticosterone, between rural and urban songbirds despite predictions that urban habitats could impact stress reactivity (Partecke et al, 2006;Bonier et al, 2007;Schoech et al, 2007;Fokidis et al, 2009Fokidis et al, , 2011Atwell et al, 2012;Bonier, 2012;Foltz et al, 2015a). Nor have consistent differences been reported in levels of testosterone, a hormone traditionally thought to promote aggression in vertebrates (Partecke et al, 2005;Fokidis et al, 2011;Deviche and Davies, 2013;Atwell et al, 2014;Davies and Sewall, 2016;. Failure to find differences in circulating hormone levels suggest that reliable behavioral differences may be underpinned by deeper brain mechanisms, yet little work has explored how urbanization and neural function may be interrelated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations